Trends in Troponin‐Only Testing for AMI in Academic Teaching Hospitals and the Impact of Choosing Wisely®. Issue 12 (20th September 2017) - Prochaska, Micah T.; Hohmann, Samuel F.; Modes, Matthew; Arora, Vineet M.
Abstract : BACKGROUND: Identifying hospitals that are both early and consistent adopters of high‐value care can help shed light on the culture and practices at those institutions that are necessary to promote high‐value care nationwide. The use of troponin to diagnose acute myocardial infarction (AMI), and not to test for myoglobin or creatine kinase‐MB (CK‐MB), is a high‐value recommendation of the Choosing Wisely ® campaign. OBJECTIVE: To examine the variation in cardiac biomarker testing and the effect of the Choosing Wisely ® troponin‐only recommendation for the diagnosis of AMI. DESIGN: A retrospective observational study using administrative ordering data from Vizient's Clinical Database/Resource Manager. SETTING: Ninety‐one academic medical centers from the fourth quarter of 2013 through the third quarter of 2016. PATIENTS: Hospitalized patients with a principal discharge diagnosis of AMI. INTERVENTION: The Choosing Wisely ® recommendation to order troponin‐only testing to diagnose AMI was released during the first quarter of 2015. RESULTS: In 19 hospitals, troponin‐only testing was consistently ordered to diagnose AMI before the Choosing Wisely ® recommendation and throughout the study period. In 34 hospitals, both troponin and myoglobin/CK‐MB were ordered to diagnose AMI even after the Choosing Wisely ® recommendation. In 26 hospitals with low rates of troponin‐only testing before the Choosing Wisely ® recommendation, the release of the recommendation was associated with a statistically significant increase in the rate of troponin‐only testing to diagnose AMI. CONCLUSION: In institutions with low rates of troponin‐only testing prior to the Choosing Wisely ® recommendation, the recommendation was associated with a significant increase in the rate of troponin‐only testing.